Technological Innovation Across Nations Applied Studies of Coevolutionary Development - van Geenhuizen, Marina; Watanabe, Chihiro; Jauhari, Vinnie; Masurel, Enno (Springer Berlin Heidelberg : Imprint: Springer, 2009)
The book offers an interesting blend of applied state-of-the-art studies of coevolutionary development of institutions, innovation diffusion and innovative entrepreneurship, not published anywhere else. It can firstly be classified as belonging to mainstream endogenous growth studies on the country level, and secondly, to mainstream evolutionary studies. What the themes in the book share is attention for institutional change in a frame of coevolutionary dynamics to elucidate differences over time and differences between countries in technological innovation and economic growth. The book contains solid applied work in this area and is mainly about information technology and electronics industry (for example, PC manufacturing); however, biotechnology is also included. In addition, the book has a wide geographic scope including a focus on the US, China, Japan, India and the Netherlands, as well as many cross-country comparisons. Part I (Adoption of Information Technology in National Institutional Systems) presents studies of historical development trajectories and/or country specific institutional circumstances of innovation diffusion. Part II (Institutional Systems, Entrepreneurship, Knowledge Transfer and Learning) is devoted to the development of institutions, and policies and practice of technology transfer and utilization by companies, including an evolutionary growth path of technology incubators.